2015
DOI: 10.1073/pnas.1503500112
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-B promotes cancer metastasis through a VEGF-A–independent mechanism and serves as a marker of poor prognosis for cancer patients

Abstract: The biological functions of VEGF-B in cancer progression remain poorly understood. Here, we report that VEGF-B promotes cancer metastasis through the remodeling of tumor microvasculature. Knockdown of VEGF-B in tumors resulted in increased perivascular cell coverage and impaired pulmonary metastasis of human melanomas. In contrast, the gain of VEGF-B function in tumors led to pseudonormalized tumor vasculatures that were highly leaky and poorly perfused. Tumors expressing high levels of VEGF-B were more metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
110
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 45 publications
5
110
1
Order By: Relevance
“…There are many studies on the biological function and intracellular signal transduction mechanism of VEGF and its receptors in tumour angiogenesis (Rivera & Bergers 2015), and the possibility of promoting some tumour metastasis (Yang et al 2015;Zarkada et al 2015). The biological activity of VEGF is mainly regulated by two tyrosine kinase receptors of VEGFR-1 (Flt-1) and VEGFR-2 (KDR/Flk-1).…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies on the biological function and intracellular signal transduction mechanism of VEGF and its receptors in tumour angiogenesis (Rivera & Bergers 2015), and the possibility of promoting some tumour metastasis (Yang et al 2015;Zarkada et al 2015). The biological activity of VEGF is mainly regulated by two tyrosine kinase receptors of VEGFR-1 (Flt-1) and VEGFR-2 (KDR/Flk-1).…”
Section: Discussionmentioning
confidence: 99%
“…For example, upregulated lncRNA ENST00000447028 was found to be located near VEGF-B mRNA. VEGF-B mRNA was reported by Yang et al to take part in the resistance of lung cancer cells to the chemotherapeutic drug EGFR-TKI (29). We found that VEGF-B mRNA was strongly upregulated, therefore, ENST00000447028 may influence paclitaxel resistance by regulating VEGF-B mRNA.…”
Section: Discussionmentioning
confidence: 54%
“…However, the VEGF-B also retarded tumor growth in the RIP1-Tag2 mouse of pancreatic neuroendocrine tumorigenesis, 6 and the reduced blood perfusion in VEGF-B-T241 tumors might explain, at least in part, the anti-tumor growth effect. 105 The antigrowth effect might also be accounted for the approximate 15% heavier weight displayed in the VEGF-B −/− mice. 6 , 13 The VEGFR-1 may explained the antigrowth and antiangiogenic effect, since it is served as the decoy receptor of VEGF-A.…”
Section: Introductionmentioning
confidence: 99%
“…106 The VEGFR-1 had a negative role in developmental vascularization, and VEGFR-1 −/− embryos died early due to VEGF-A dependent vessels overgrowth and disorganization. 107 Moreover, the VEGF-B advanced tumor invasiveness both in HCC patients 108 and mouse tumors, 105 via remodeling of the tumor microvasculature, leading to leaky vascular networks that are highly permissive for invasion. 105 So, VEGF-B might have paradoxical roles in cancer initiation and further progression, inhibiting growth and promoting metastasis, which insinuated the uncoupling of the metastasis and primary tumor growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation